Lactiplantibacillus plantarum postbiotics: alternative of antibiotic growth promoter to ameliorate gut health in broiler chickens - Chang, Hui Mei; Loh, Teck Chwen; Foo, Hooi Ling; Teik, Eric Chung Lim (Frontiers Research Foundation, 2022)
The postbiotic produced from Lactiplantibacillus plantarum has been revealed as a potential alternative to antibiotic growth promoters (AGP). It helps to stimulate growth performance, improve nutrient digestibility, intestinal histomorphology, immune response, and improve meat quality in livestock. However, there is a paucity of information on the effects of L. plantarum postbiotic produced by formulated media on the gut health and immune response. Therefore, this study was conducted by using three strains of dietary L. plantarum postbiotics to determine the growth performance, intestinal histomorphology, intestinal mucin production, and immune status in broiler chickens. A 245 male Cobb 500-day-old birds were assigned randomly to five treatments, namely, NC: basal diet only (negative control), OTC: basal diet + 0.01% (w/w) oxytetracycline (positive control), RG11: basal diet + 0.1% (v/w) Postbiotic RG11, RI11: basal diet + 0.1% (v/w) Postbiotic RI11, and RS5: basal diet + 0.1% (v/w) Postbiotic RS5. The body weight and feed intake were taken weekly. The small intestine and its mucus, ceca digesta were collected on days 21 and 42. Fresh excreta for crude mucin production were collected 3 days before slaughter on day 42. From the findings, RS5 recorded a significant highest (p < 0.05) final body weight, body weight gain, and significant lowest (p < 0.05) feed conversion ratio. The concentrations of glutathione peroxidase, superoxide dismutase (SOD), acidic mucin, sulfated mucin, and intestinal trefoil factor were significantly higher (p < 0.05) in the birds fed with RI11 and RS5. Postbiotics RI11 and RS5 had up-regulated expression of intestinal Mucin 2, occludin, and secretory immunoglobulin A. The antibiotic-fed chickens also showed a reduced (p < 0.05) total bacteria and Bifidobacterium population but a significantly increased (p < 0.05) the population of Escherichia coli in the jejunum. In conclusion, the supplementation of L. plantarum postbiotic can be used to substitute AGP as it promoted growth performance, mucin production, ameliorated tight junction permeability, and immune status in broiler chickens due to improved gut health and beneficial bacteria colonization.